Improvement in postoperative mortality in elective gastrectomy for gastric cancer: Analysis of predictive factors in 1066 patients from a single centre. Issue 7 (July 2017) - Norero, E.; Vega, E.A.; Diaz, C.; Cavada, G.; Ceroni, M.; Martínez, C.; Briceño, E.; Araos, F.; Gonzalez, P.; Baez, S.; Vinuela, E.; Caracci, M.; et al.
Abstract: Background: Gastrectomy represents the main treatment for gastric adenocarcinoma. This procedure is associated with substantial morbidity and mortality. The aim of this study was to evaluate the postoperative mortality changes across the study period and to identify predictive factors of 30-day mortality after elective gastrectomy for gastric cancer. Methods: This was a retrospective cohort study of a prospective database from a single centre. Patients treated with an elective gastrectomy from 1996 to 2014 for gastric adenocarcinoma were included. We compared postoperative mortality between four time periods: 1996–2000, 2001–2005, 2006–2010, and 2011–2014. Univariate and multivariate analyses were applied to identify predictors of 30-day postoperative mortality. Results: We included 1066 patients (median age 65 years; 67% male). The 30-day mortality rate was 4.7%. Mortality decreased across the four time periods; from 6.5% to 1.8% ( P = 0.022). In the univariate analysis, age, ASA score, albumin <3.5, multivisceral resection, splenectomy, intrathoracic esophagojejunal anastomosis, R status, and T status were significantly associated with postoperative mortality. In the multivariate analysis, ASA class 3 (OR 10.06; CI 1.97–51.3; P = 0.005) and multivisceral resection (OR 1.6; CI 1.09–2.36; P = 0.016) were associated with higher postoperative 30-day mortality; surgery between 2011 and 2014 was associated with lower postoperative 30-day mortality (OR 0.55; CI 0.33–0.15; P = 0.030). Conclusion: There was a decrease in postoperative 30-day mortality during this 18-year period at our institution. We have identified ASA score and multivisceral resection as predictors of 30-day mortality for elective gastrectomy for cancer.